Her way : biographies of women for young people - Siegel, Mary-Ellen.; Basaldua, Tim. (Chicago : American Library Association, 1976)
A collection of 260 short profiles and bibliographies of notable women throughout history and an additional bibliography of over 300 collective biographies of women.
Includes bibliographical references and index.
Keywords: Women -- Biography -- Juvenile literature; Women -- Juvenile literature -- Bio-bibliography.; Biography; Women -- Bio-bibliography.